2022
DOI: 10.1039/d2dt00491g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ring size of TMC ligands in controlling C–H bond activation by metal-superoxo species

Abstract: Metal-superoxo species are very important in carrying many metal-mediated catalytic transformation reactions. Such catalytic reactivity is affected by many factors such as by nature of metal ions and ring size...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 110 publications
1
8
0
Order By: Relevance
“…There are two possible spin states for chromium(IV)-oxo species, i.e., 3 Cr hs -Int and 1 Cr ls -Int, and our results show that the high-spin state ( 3 Cr hs -Int) is found as the ground state, which is in agreement with the previous studies. 73,78 The computed Cr-O bond length was found to be 1.715 Å, which is in agreement with the experimental observation. 95 Chromium-oxo species also play an important role during hydrogen and oxygen atom transfer reactions.…”
Section: Chromium(iii) Hydroperoxo Speciessupporting
confidence: 86%
See 4 more Smart Citations
“…There are two possible spin states for chromium(IV)-oxo species, i.e., 3 Cr hs -Int and 1 Cr ls -Int, and our results show that the high-spin state ( 3 Cr hs -Int) is found as the ground state, which is in agreement with the previous studies. 73,78 The computed Cr-O bond length was found to be 1.715 Å, which is in agreement with the experimental observation. 95 Chromium-oxo species also play an important role during hydrogen and oxygen atom transfer reactions.…”
Section: Chromium(iii) Hydroperoxo Speciessupporting
confidence: 86%
“…In our previous studies, we have performed DFT calculations with the two possible isomers based on the orientation of the methyl groups of the TMC ring (either syn or anti to the superoxo unit), and we found that the anti isomer is more stable than the syn isomer. 73 Thus, here, we performed the calculations on the 3d metal hydroperoxo species with a 14-TMC ligand having chlorine at the position trans to the hydroperoxo, i.e., the anti isomer, and studied the structure and energetics of the metal hydroperoxo species, O⋯O bond cleavage and formed metal-oxo species, followed by a comparative study. Here, we started the calculations with the chromium hydroperoxo species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations